Արշարունյաց եպիսկոպոսական թեմը (IV–XI դդ.) - Մանուչարյան, Աշոտ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Епархия Аршаруник – одна из старейших епархий Армении, образованная Св. Григорием Просветителем во втором епархиальном отделении. В середине IV века, во время правления католикоса Св. Нерсеса Великого, она была присоединена к епископству Багреванда. Он стал главным епископатом страны, когда католикос Св. Саак Партев, в 432 г. вернувшись из Персии, поселился в провинции Багреванд. Известными епископами Багреванда в этот период были философ V в. Езник Кохбаци и родоначальник армянской историографии Мовсес Хоренаци. После смерти Мовсеса Хоренаци (490 г.) епархия Аршаруник отделилась от Багреванда и действовала самостоятельно. В период с 490 г. до собрания Маназкерта (726 г.) из источников известны имена 12 епископов Аршаруника. Самым известным из них был философ Григор Аршаруни (683–726), который был помощником Армянского католикоса Св. Иоанна III Одзунского. В епархии Аршаруник были высшие учебные заведения (Ширакская семинария, духовная школа Аршаруника), где преподавали математик, космолог Анания Ширакаци (610–685), философ, переводчик Пилон Тиракаци. После 726 г. епархия Аршаруник пришла в упадок. Она возродилась во время правления Багратидов (874 / 855–1045). Самым известным епископом Аршаруника в этот период был Хачик, впоследствии ставший Армянским католикосом – Хачик I Аршаруни (972–990). Во время его правления знаменитый архитектор Трдат построил католикосскую церковь Аргины. Вскоре после падения династии Багратидов (1045 г.) епископство Аршаруник прекратило свое существование. The Diocese of Arsharunik is one of the oldest dioceses in Armenia, formed by St. Gregory the Illuminator in the second diocesan department. In the middle of the 4th century, during the reign of Catholicos St. Nerses the Great, it was annexed to the bishopric of Bagrevand. It became the main episcopate of the country when Catholicos St. Sahak Partev returning from Persia in 432 AD, settled in the province of Bagrevand. The famous bishops of Bagrevand during this period were the 5th century philosopher Yeznik Koghbatsi and the patriarch of the Armenian historiography Movses Khorenatsi. After the death of Movses Khorenatsi (490 AD), the diocese of Arsharunik separated from Bagrevand and acted independently. From 490 AD to the Council of Manazkert (726), the names of 12 bishops of Arsharunik are known from sources. The most famous of them was philosopher Grigor Arsharuni (683–726), who was an assistant to the Armenian Catholicos St. John III of Odzun. In the diocese of Arsharunik there were higher educational institutions (Shirak seminary, theological school of Arsharunik), where mathematician, cosmologist Anania Shirakatsi (610–685), philosopher, translator Pilon Tirakatsi taught. After 726, the diocese of Arsharunik fell into decay. It was revived during the reign of the Bagratids (874/855–1045). The most famous bishop of Arsharunik during this period was Khachik, who later became the Armenian Catholicos Khachik I of Arsharuni (972–990). During his reign, famous architect Trdat built the Cathedral of Argina. Soon after the fall of the Bagratid dynasty (1045), the bishopric of Arsharunik ceased to exist.
Keywords: Հայոց եկեղեցի